IMUNISASI PROTEIN ADHESIN 38-KDA MYCOBACTERIUM TUBERCULOSIS LEWAT RONGGA MULUT TERKAIT SEL T CD8+ DI PARU - Arthamin, Maimun Z; Gani, Agus A; Issiyah, Nurani; Santoso, Sanarto (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2012)
The efficacy of Bacillus Calmette-Guerin (BCG), vaccine against tuberculosis (TB), varies widely, from 0 to 90%; and BCG mainly activates CD4+ T cells, but it fails to activate CD8+ T cells. From the previous study, 38-kDa protein is an adhesin protein. CD8+ T cells play the role in controlling Mycobacterium tuberculosis (M.tb) infection and contribute to the memory immunity. The objective of this study was to determine effect of oral immunization by 38-kDa adhesin protein of M.tb to increase the level of CD8+ T cells in the lung of BALB/c mice. This study used an experimental with post test control group design. The mice were divided into six groups (each group consist of 4 samples), where Group 1: were immunization orally with 100 μg 38-kDa adhesin protein of M.tb and 12 μg ISCOMs. Followed by group 2: 100 μg 38-kDa adhesin protein of M.tb, group 3: 50 μg 38-kDa adhesin protein of M.tb and 12 μg ISCOMs, and group 4: 50 μg 38-kDa adhesin protein of M.tb. Group 5: 12 μg ISCOMs. Group 6: Control. In this study was found increased level of CD8+ T cells in the lung of BALB/c mice after orally immunization with 38-kDa adhesin protein of M.tb. The highest level of CD8+ T cells was on group 1, p=0.000. Also there were found significant differences among the immunized groups, except group 2 and 3, as well as group 5 and 6 also. It can be concluded in this study that oral immunization with 38-kDa adhesin protein of M.tuberculosis could increase the level of CD8+ T cells in the lung of BALB/c mice.